A bibliometric study of pool fire related publications. (January 2020) - Liu, Jiahao; Li, Jie; Fan, Chuangang
Abstract: Pool fire is a common form of fire, which is constantly investigated along with the development of fire science and is also comprehensively employed as stable fire sources in examining other fire scenarios such as building and tunnel fires. According to the records in Science Citation Index Expanded database in the Web of Science Core Collection, a total of 1073 articles or reviews related to pool fires have been published from 1966 to 2019. In order to have a better understanding of knowledge structure of this topic and further identify its development history and currently popular concerns, a bibliometric analysis of pool fire research is conducted by means of visualization software VOSviewer and CiteSpace. This work visually provides a comprehensive overview of pool fire research in terms of annual publication output, source journals, productive countries/regions, authors and their cooperation network, subject terms, and reference co-citation analysis. The analysis provides networks of co-cited references, authors, countries, subject terms, and their respective clusters, indicating their ranking in contributions to the pool fire related publications. The results can be applied to enhance the understanding of pool fire research and support further work in this area. Highlights: A total of 1073 papers related to pool fires are published from 1966 to 2019. Key information of pool fire related publications was visualized and analyzed. Pool fires subject to wind and low-pressure environment are recently hot topics.